Efektivitas Asam Askorbat Buah Alpukat (Persea americana Mill.) Terhadap Pemutihan Gigi - Wika Putri Rizkiah; Etny Dyah Harniati; Lira Wiet Jayanti (Jurnal Material Kedokteran Gigi, 2021)
Teeth discoloration has been complained by most of Indonesians. A treatment of teeth discoloration can be overcome by using a bleaching treatment. Bleaching itself, can be done using a natural ingredients, for instance avocado (Persea americana Mill.),which contained an ascorbic acid for a dental bleaching. The aim of this study is to find out the effectiveness of avocado with concentrations of 30%, 70%, and 100% on a teeth bleaching. It is a laboratory experimental research using a pretest-posttest control group design. The sample used are 24 post-extraction of premolar teeth, and ascorbic acid which was taken from the avocado by an isolation method. The teeth soaked in a black tea for 6 days and replaced every 2 days, then soaked with ascorbic acid in the avocado extract 30%, 70%, 100%, and control aquades for 3 days.The degree of teeth color was measured by using a spectrophotometer. The data analysis used a discrimination test with One Way Anova and further discrimination test with Pos Hoc Anova. The results of discrimination test with One Way Anova showed the significant value was 0,019 (p<0,05), which means there was difference colour between before and after the soaking teeth treatment using the ascorbic acid in avocado with concentrations of 30%, 70%, and 100%. Based on Pos Hoc Anova test, showed that 30% and 100% concentrations of ascorbic acid is more effective than the aquades. As the 100% concentration of ascorbic acid showed a demineralization. Therefore the 30% concentration of ascorbic acid is the most effective. The ascorbic acid in avocado extract (Persea americana Mill.) with 30%, 70%, dan 100% concentrations is effective for a dental bleaching.